SDG Financing Options in Rwanda : A Post-Pandemic Assessment - Lledo, Victor (IMF Working Papers; Working Paper ;, 2021)
This paper uses a novel macroeconomic framework to identify policy and financing options to help Rwanda achieve its sustainable development goals (SDGs). Under current policies, Rwanda would meet its SDGs right after 2050. Active policies that combine fiscal reforms and higher private sector participation could fulfill more than one third of Rwanda's post-pandemic SDG financing gap, enabling the country to meet its SDG targets by 2040. For Rwanda to meet its SDGs by 2030, active policies would need to be complemented with about 13 3/4 percentage points of GDP in additional resources annually until then.